Cultivation and Genomic Analysis of “Candidatus Nitrosocaldus islandicus,” an Obligately Thermophilic, Ammonia-Oxidizing Thaumarchaeon from a Hot Spring Biofilm in Graendalur Valley, Iceland - Daebeler, Anne; Herbold, Craig W.; Vierheilig, Julia; Sedlacek, Christopher J.; Pjevac, Petra; Albertsen, Mads; Kirkegaard, Rasmus H.; de la Torre, José R.; Daims, Holger; Wagner, Michael (Frontiers in Microbiology, 2018)
Ammonia-oxidizing archaea (AOA) within the phylum Thaumarchaeota are the only known aerobic ammonia oxidizers in geothermal environments. Although molecular data indicate the presence of phylogenetically diverse AOA from the Nitrosocaldus clade, group 1.1b and group 1.1a Thaumarchaeota in terrestrial high-temperature habitats, only one* enrichment culture of an AOA thriving above 50 °C has been reported and functionally analyzed. In this study, we physiologically and genomically characterized a newly discovered thaumarchaeon from the deep-branching Nitrosocaldaceae family of which we have obtained a high (~85 %) enrichment from biofilm of an Icelandic hot spring (73 °C). This AOA, which we provisionally refer to as “Candidatus Nitrosocaldus islandicus”, is an obligately thermophilic, aerobic chemolithoautotrophic ammonia oxidizer, which stoichiometrically converts ammonia to nitrite at temperatures between 50 °C and 70 °C. “Ca. N. islandicus” encodes the expected repertoire of enzymes proposed to be required for archaeal ammonia oxidation, but unexpectedly lacks a nirK gene and also possesses no identifiable other enzyme for nitric oxide (NO) generation*. Nevertheless, ammonia oxidation by this AOA appears to be NO-dependent as “Ca. N. islandicus” is, like all other tested AOA, inhibited by the addition of an NO scavenger. Furthermore, comparative genomics revealed that “Ca. N. islandicus” has the potential for aromatic amino acid fermentation as its genome encodes an indolepyruvate oxidoreductase (iorAB) as well as a type 3b hydrogenase, which are not present in any other sequenced AOA. A further surprising genomic feature of this thermophilic ammonia oxidizer is the absence of DNA polymerase D genes* – one of the predominant replicative DNA polymerases in all other ammonia-oxidizing Thaumarchaeota. Collectively, our findings suggest that metabolic versatility and DNA replication might differ substantially between obligately thermophilic and other AOA.